Investigation of CACNA1I Cav3.3 Dysfunction in Hemiplegic Migraine - Maksemous, Neven; Blayney, Claire D.; Sutherland, Heidi G.; Smith, Robert A.; Lea, Rod A.; Tran, Kim Ngan; Ibrahim, Omar; McArthur, Jeffrey R.; Haupt, Larisa M.; Cader, M. Zameel; Finol-Urdaneta, Rocio K.; Adams, David J.; et al. (Frontiers in Molecular Neuroscience, 2022)
Familial hemiplegic migraine (FHM) is a severe neurogenetic disorder for which three causal genes, CACNA1A, SCN1A, and ATP1A2, have been implicated. However, more than 80% of referred diagnostic cases of hemiplegic migraine (HM) are negative for exonic mutations in these known FHM genes, suggesting the involvement of other genes. Using whole-exome sequencing data from 187 mutation-negative HM cases, we identified rare variants in the CACNA1I gene encoding the T-type calcium channel Cav3.3. Burden testing of CACNA1I variants showed a statistically significant increase in allelic burden in the HM case group compared to gnomAD (OR = 2.30, P = 0.00005) and the UK Biobank (OR = 2.32, P = 0.0004) databases. Dysfunction in T-type calcium channels, including Cav3.3, has been implicated in a range of neurological conditions, suggesting a potential role in HM. Using patch-clamp electrophysiology, we compared the biophysical properties of five Cav3.3 variants (p.R111G, p.M128L, p.D302G, p.R307H, and p.Q1158H) compared to wild-type (WT) channels expressed in HEK293T cells. We observed numerous functional alterations across the channels with Cav3.3-Q1158H showing the greatest differences compared to WT channels, including reduced current density, right-shifted voltage dependence of activation and inactivation, and slower current kinetics. Interestingly, we also found significant differences in conductance properties exhibited by the Cav3.3-R307H and -Q1158H variants compared to WT channels under conditions of acidosis and alkalosis. In light of these data, we suggest that rare variants in CACNA1I may contribute to HM aetiology.